The Formation of Students' Religious Character through Islamic Religious Eduction Learning Asma'ul Husna Material at Ma'arif 1 Middle School - Nazila, Laili Nazila; Aziz Q, Ikhwan; Ningsih, Eka Fitria (International Journal on Advanced Science, Education, and Religion, 2025)
This research aims to determine the process of implementing the habit of reading the Asmaul Husna, the supporting and inhibiting factors in the process of implementing the habit, in order to shape the religious character of students at SMP Ma'arif 1 Metro. The type of research used is field research with a qualitative descriptive approach. The data collection method was carried out in three stages, namely: Observation, interviews and documentation. Meanwhile, the data analysis techniques are: data reduction, data presentation, and drawing conclusions. The results of this research found that: The results of the research show that the formation of religious character is carried out through synergy between routine religious activities (such as congregational midday prayers, reading Surah Yasin and Asma'ul Husna), teacher example, and integrating character values in the learning process. Even though there are obstacles such as low student awareness and lack of consistency in learning, teachers still play an important role as motivators and role models. The gradual cultivation of religious character shows a positive impact on changes in student behavior, both in the school environment and in everyday life. These findings emphasize the importance of PAI learning as an effective medium in forming students' religious character holistically.